Assessing the toxicity of ionic liquids – Application of the critical membrane concentration approach. (September 2017) - Bittermann, Kai; Goss, Kai-Uwe
Abstract: Charged organic chemicals are a prevailing challenge for toxicity modelling. In this contribution we strive to recapitulate the lessons learned from the well-known modelling of narcosis (or baseline toxicity) of neutral chemicals and apply the concept to charged chemicals. First we reevaluate the organism- and chemical independent critical membrane concentration causing 50% mortality, . c mem t o x, based on a critical revision of a previously published toxicity dataset for neutral chemicals. In accordance to values reported in the literature we find a mean value for c mem t o x of roughly 100 mmol/kg (membrane lipid) for a broad variety of 42 aquatic organisms (333 different chemicals), albeit with a considerable scatter. Then we apply this concept to permanently charged ionic liquids (ILs). Using COSMO mic, a quantum mechanically based mechanistic model that makes use of the COSMO-RS theory, we predict membrane-water partition coefficients ( K mem/w ) of the anionic and cationic IL components. Doing so, c mem t o x ( t o t a l ) for permanently charged ILs can be estimated assuming independent, concentration additive contributions of the cationic and its respective anionic species. The resulting values for some of the toxicity data for ionic liquids are consistent with the expected range for baseline toxicity for neutral chemicals while other values are consistently greater or smaller. Based on the calculation of toxic ratios we identify ILs that exert a specific mode of toxic action. Limitations of the modelling approach especially but not exclusively due to the use of nominal concentrations instead of freely-dissolved concentrations in the published literature are critically discussed. Graphical abstract: Highlights: Toxic membrane concentration of neutrals confirmed (333 chemicals, 42 organisms). Concentration of ∼100 mmol/kg (membrane lipid) causes toxic effect. Kmem/w values of ionic liquids (ILs) predicted with COSMO mic . ILs exhibit critical membrane concentrations in the range of neutrals. Critical discussion of artefacts that hamper definite conclusions.